Strict liability offences : are they not in conflict with purpose of sentence and constitutional expectations? - Rantsane, Ditaba Petrus (North-West University (South Africa)., 2011)
Aim of the study: The intention of this study is, generally, to show that strict liability has no place in a democratic society based on human dignity, equality and freedom , as it undermines the purpose of sentence and, more importantly, the spirit of the Constitution. The main objective is to make recommendations to the Constitutional Court regarding the uncertainties surrounding the constitutionality of strict liability offences. This will , hopefully, lead to this principle being declared unconstitutional. Research procedure and methodology: Various methods will be used to achieve the aim of this research , including extensive reading and critical analysis of books, journal articles , internet sources and reported cases on the topic. In addition , the approach of foreign legal systems to strict liability offences will be explored in order to establish whether such systems offer us guidance on how to deal with strict liability offences without contravening the provisions of the Constitution. Conclusion and recommendations: As with other countries, strict liability offences are part of South African criminal law, with fault or mens rea forming an integral part of our criminal justice system. In the past it was accepted practice that mens rea should be proved beyond reasonable doubt before a person could be found guilty of a crime. This was the position until the introduction of strict liability offences into English law during the 19th century. This introduction brought about a dramatic change in perspective, with mens rea forming an important element of criminal liability. This controversial development in the law was met with two opposing opinions, that is, those in favour of this practice and those against it. The argument in favour of strict liability was to the effect that these are statutory offences and not real criminal offences, and , as such, they are only invoked for public welfare offences. They further argue that strict liability offences attract lenient sentences. The critical response to these justifications has been that the distinctions between sanctions for acts which are morally wrong and prohibited by law do not change the fact that the sanctions are criminal in essence and that criminal sanctions without blameworthiness have little support in either deterrent or retributive theory. The opposition to strict liability arose in South Africa as far back as the 1970s with the Viljoen Commission enquiry into the South African penal system. Since the inception of strict liability, the law has evolved, with the South African legal system changing from Parliamentary sovereignty to constitutional supremacy. The effect of the change has been that the law practised in South Africa is supposed to be aligned with the Constitution. The Constitution has also authorised courts, when developing the common law or interpreting statutes, to consider international and foreign law. Accordingly, consultation has taken place with other countries on the way in which they approach strict liability offences. The research revealed that there are similarities in the criminal law approaches of all the countries consulted in that they all have a high regard for the element of mens rea. However, there is also an acceptance that the introduction of strict liability is necessary to protect people from harm . Courts from these countries are of the view that it should not be left up to them to interpret whether the legislature requires the offence to be strict liability or not. Consequently, they prefer the legislature to make its intentions clear on the statute. This study shares the view of Snyman that the principle of strict liability will not pass the constitutional muster. The argument held by this study is that strict liability infringes on the right to remain silent, the presumption of innocence, privilege against self-incrimination and the right to a fair trial, as enacted in the Constitution.
LLM, North-West University, Mahikeng Campus
Keywords: Strict liability; Constitution; Apartheid; Punishment; Colonialism; Mens rea; Transformative constitutionalism; Crime; Colonial regime; Vicarious liability; Common law; Defamation; Racial segregation; Public welfare offences; Actus reus; Due diligence; Regulatory offences; Fundamental rights; Sanctions; Retributive theory; Reformative theory; Preventive theory; Deterrence theory; Sentence; Minimum sentence; Restorative justice; Guilty mind; Fault